2021
DOI: 10.1016/j.redox.2021.102101
|View full text |Cite
|
Sign up to set email alerts
|

The multi-functional roles of forkhead box protein O in skin aging and diseases

Abstract: Forkhead box, class O (FoxO) family members are multifunctional transcription factors that are involved in several metabolic processes, including energy metabolism, apoptosis, DNA repair, and oxidative stress. However, their roles in skin health have not been well-documented. Recent studies have indicated that FoxOs are important factors to control skin homeostasis and health. The activation or deactivation of some FoxO family members is closely related to melanogenesis, wound healing, acne, and melanoma. In t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 100 publications
0
7
0
Order By: Relevance
“…Like IL-17, IL-22 also enhances inflammation by inducing various cytokines, chemokines, and AMPs 29 . Other regulators such as Rho-Associated Protein Kinase 2, which is involved in the differentiation and proliferation of keratinocytes 40 , and Forkhead Box Protein O1, which is involved in the motility of keratinocytes 41 , also show decreased activity z score by NB-UVB treatment in the CE skin.…”
Section: Discussionmentioning
confidence: 99%
“…Like IL-17, IL-22 also enhances inflammation by inducing various cytokines, chemokines, and AMPs 29 . Other regulators such as Rho-Associated Protein Kinase 2, which is involved in the differentiation and proliferation of keratinocytes 40 , and Forkhead Box Protein O1, which is involved in the motility of keratinocytes 41 , also show decreased activity z score by NB-UVB treatment in the CE skin.…”
Section: Discussionmentioning
confidence: 99%
“…FOXO3a, a transcriptional factor, maintains cellular homeostasis and extends lifespan via regulation of the expression of multiple downstream target genes that are involved in energy metabolism, redox status, mitochondrial functions, autophagy, stress resistance, cell proliferation, DNA repair, and telomere maintenance [ 52 , 53 , 77 , 78 ]. Previous studies have indicated that FOXO3a participates in the maintenance of skin homeostasis and skin health [ 79 , 80 ]. Therefore, activation of FOXO3a is a promising therapeutic strategy for reducing skin aging [ 50 , 81 ].…”
Section: Discussionmentioning
confidence: 99%
“…Among them, PI3K-AKT, FoxO, TNF, and MAPK signaling pathways were enriched in more than 10 targets, suggesting that YQD has a certain intervention effect on these signaling pathways. It was reported that these pathways were involved in the regulation of melanin production [50][51][52][53][54][55] . The main vitiligo related pathways involved in YQD and the relationship between active components and pathway targets were shown in Fig.…”
Section: Discussionmentioning
confidence: 99%